Probabilistic analysis of creep of cement paste at nanogranular level - Jacob, Susan; Anoop, M.B.; Rao, K. Balaji; Kurian, Babu; Iyer, Nagesh R. (Journal of Structural Engineering, 2024)
Probabilistic analysis of rate of creep and the creep strain in the individual C-S-H phases of cement paste (which is considered to be the origin of concrete creep), taking into account the shape and dispersion of packing densities of individual phases, is presented. An attempt is also made to determine the creep behaviour of the composite (i.e., the cement paste), where the C-S-H phases co-exist, using the rule of mixtures. From the results obtained from the present study, it is noted that: i) the mean values of creep rate and creep strain increase with increase in water-cement ratio, and, ii) histograms of creep rate and creep strain obtained using HD equivalence are uni-modal when compared to those obtained using LD equivalence, suggesting that appropriate homogenization schemes based on the behaviour of the individual phases has to be obtained in the future.